Coculture of tumor organoids with pathogenic microorganisms: a novel system to mimic in vivo pathogenic infection - Zhang, Xue; Sun, Shulan; Cheng, Siqi; Dai, Junze; Du, Furong; Wang, Jingrui; Wei, Dan; Yan, Yichao; Liu, Yefu (Frontiers in Cellular and Infection Microbiology, 2025)
Since the early 20th century, there has been extensive discussion on the intricate relationship between pathogenic infection and tumors. However, most studies on host-pathogen interactions are performed based on the in-vitro culture, immortalized cell lines or animal experiments. A significant challenge lies in accurately establishing a coculture model between tumors and pathogens under the three-dimensional (3D) context. Recently, the hybrid model system that incorporates 3D tumor organoids and two-dimensional cell lines have been gradually used to analyze the intricate relationship between pathogens and tumors, and several coculture techniques for tumor organoids and pathogens have also been developed. Therefore, this study systematically reviewed the preparation and identification of tumor organoids, coculture techniques with pathogens, and their clinical applications, aiming to further understand and simulate the interaction mechanism between the hosts and pathogens.